Potensi Pengembangan Budidaya Ulat Sutera di Areal KPHP Model Awota - Emban Ibnurusyd Mas'ud; Muh. Ichwan Kadir; Hasanuddin Molo; Muh. Tahnur; Hardiyanti Hardiyanti; Selamet Riyadi (Jurnal Hutan dan Masyarakat, 2017)
The dialectics between local government interest versus the central government in forestry sector are the main topics of forestry today. Natural silk management is the interest of local government that has been assimilated into Forest Management Unit (KPH)in the form of KPHP Awota Model Awota. Until now, there is no scientific study on the potential of silkworm cultivation development in this areal. Therefore this study aims to analyze the potential of silkworm cultivation development. This potential in question is the institutional system, biophysical potential, environmental potential, market potential and financial value. The results showed that the development of silkworm cultivation in KPHP Awota Model area has the advantage of biophysical potential, environmental potential, marketing potential and financial value. However, this activity has an obstacles in the institutional issues primarily in the management of silkworm cultivation from upstream to downstream sectors.